Performance enhancement and the young athlete: Mapping the landscape and navigating future directions - Harwood, C. G.; Thrower, S. N. (Kinesiology Review, 2019)
The aim of this paper is to provide a comprehensive narrative review of extant scientific knowledge on the effectiveness of performance-enhancement-based interventions in youth sport settings. Specifically, the authors explore the effects of psychological interventions on the sport performance of young athletes (18 yr of age or under). Drawing on over 80 published studies that have attempted to enhance young athletes` performances using a range of methodological and strategic approaches, four main clusters of research are presented. These clusters include single-strategy psychological-skills-training (PST) interventions, multimodal PST interventions, alternative single-strategy interventions, and alternative multimodal interventions. In each of these clusters, the landscape of work is overviewed and papers of particular methodological interest are highlighted before the authors draw out critical reflections, future research directions, and recommendations for supporting further scholarship and practice with young athletes.